2018
DOI: 10.1371/journal.pone.0205692
|View full text |Cite
|
Sign up to set email alerts
|

Novel Double Factor PGT strategy analyzing blastocyst stage embryos in a single NGS procedure

Abstract: In families at risk from monogenic diseases affected offspring, it is fundamental the development of a suitable Double Factor Preimplantation Genetic Testing (DF-PGT) method for both single-gene analysis and chromosome complement screening. Aneuploidy is not only a major issue in advanced-maternal-age patients and balanced translocation carriers, but also the aneuploidy rate is extremely high in patients undergoing in vitro fertilization (IVF), even in young donors. To adequate NGS technology to the DF-PGT str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Title and abstract screening resulted in 73 papers. Full text screening resulted in 26 publications fulfilling the inclusion criteria . No randomized controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Title and abstract screening resulted in 73 papers. Full text screening resulted in 26 publications fulfilling the inclusion criteria . No randomized controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Such a technique can be adapted to any mutation using appropriate primer spike-ins. Del Rey and colleagues have successfully combined NGS copy number analysis with large panels of common single gene conditions [ 194 ]. Alcaraz and colleagues reported a technique that combines chromosomal copy number calling with a SNP-based analysis of a mutation specific to a patient’s genetic profile, showing its feasibility in over 150 different mutations [ 195 ].…”
Section: Current Developments and Future Directions Of Pgt For Chrmentioning
confidence: 99%
“…In another NGS approach, a target enrichment gene panel with nearly 5000 Mendelian disease-associated genes (TruSight One sequencing panel) was applied on MDA-based WGA products, thereby offering direct testing of family pathogenic variant(s) plus indirect pathogenic variant detection through haplotyping of SNPs together with chromosome copy number detection through the log ratio of signal intensities, i.e., PGT-M and PGT-A together in a single workflow [57].…”
Section: Ngs For Concurrent Pgt-m and Pgt-amentioning
confidence: 99%